LexA, an SOS response repressor, activates TGase synthesis in Streptomyces mobaraensis - Shi, Xinyu; Yan, Hao; Yuan, Fang; Li, Guoying; Liu, Jingfang; Li, Chunli; Yu, Xiaobin; Li, Zilong; Zhu, Yunping; Wang, Weishan (Frontiers in Microbiology, 2024)
Transglutaminase (EC 2.3.2.13, TGase), an enzyme that catalyzes the formation of covalent cross-links between protein or peptide molecules, plays a critical role in commercial food processing, medicine, and textiles. TGase from Streptomyces is the sole commercial enzyme preparation for cross-linking proteins. In this study, we revealed that the SOS response repressor protein LexA in Streptomyces mobaraensis not only triggers morphological development but also enhances TGase synthesis. The absence of lexA significantly diminished TGase production and sporulation. Although LexA does not bind directly to the promoter region of the TGase gene, it indirectly stimulates transcription of the tga gene, which encodes TGase. Furthermore, LexA directly enhances the expression of genes associated with protein synthesis and transcription factors, thus favorably influencing TGase synthesis at both the transcriptional and posttranscriptional levels. Moreover, LexA activates four crucial genes involved in morphological differentiation, promoting spore maturation. Overall, our findings suggest that LexA plays a dual role as a master regulator of the SOS response and a significant contributor to TGase regulation and certain aspects of secondary metabolism, offering insights into the cellular functions of LexA and facilitating the strategic engineering of TGase overproducers.